The inhibition of IL-2/IL-2R gives rise to CD8+ T cell and lymphocyte decrease through JAK1-STAT5 in critical patients with COVID-19 pneumonia (2020)
Although most patients with COVID-19 pneumonia have a good prognosis, some patients develop to severe or critical illness, and the mortality of critical cases is up to 61.5%. However, specific molecular information about immune response in critical patients with COVID-19 is poorly understood. A total of 54 patients were enrolled and divided into three groups, among which 34 were common, 14 were severe, and 6 were critical. The constitution of peripheral blood mononuclear cells (PBMC) in patients was analyzed by CyTOF. The profile of cytokines was examined in plasma of patients using luminex. The IL-2 signaling pathway was investigated in the PBMC of patients by qRT-PCR. The count and percentage of lymphocytes were significantly decreased in critical patients compared to common and severe patients with COVID-19 pneumonia. The count of T cells, B cells, and NK cells was remarkably decreased in critical patients compared to normal controls. The percentage of CD8+ T cells was significantly lower in critical patients than that in common and severe patients with COVID-19 pneumonia. The expression of IL-2R, JAK1, and STAT5 decreased in PBMC of common, severe, and critical patients, but IL-2 level was elevated in severe patients and decreased in critical patients with COVID-19 pneumonia. The decrease of CD8+ T cells in critical patients with COVID-19 pneumonia may be related to the IL-2 signaling pathway. The inhibition of IL-2/IL-2R gives rise to CD8+ T cell and lymphocyte decrease through JAK1-STAT5 in critical patients with COVID-19 pneumonia.